2002
DOI: 10.14214/sf.545
|View full text |Cite
|
Sign up to set email alerts
|

Eight heuristic planning techniques applied to three increasingly difficult wildlife planning problems

Abstract: Chung, W. 2002. Eight heuristic planning techniques applied to three increasingly diffi cult wildlife planning problems. Silva Fennica 36(2): 561-584.As both spatial and temporal characteristics of desired future conditions are becoming important measures of forest plan success, forest plans and forest planning goals are becoming complex. Heuristic techniques are becoming popular for developing alternative forest plans that include spatial constraints. Eight types of heuristic planning techniques were applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 17 publications
(20 reference statements)
5
148
0
3
Order By: Relevance
“…Given that the harvested trees are the main decision, formulation of this problem through mixed integer non-linear programming was deemed quite difficult. Therefore, threshold accepting was chosen due to its speed and reputation for producing high-quality results in comparison with other heuristics [29]. Further, the results from the heuristic were generated from random initial solutions in order to develop statistically independent samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the harvested trees are the main decision, formulation of this problem through mixed integer non-linear programming was deemed quite difficult. Therefore, threshold accepting was chosen due to its speed and reputation for producing high-quality results in comparison with other heuristics [29]. Further, the results from the heuristic were generated from random initial solutions in order to develop statistically independent samples.…”
Section: Discussionmentioning
confidence: 99%
“…Threshold accepting was developed initially by Dueck and Scheuer [28] and has been applied to forest-level optimization problems in [29][30][31][32], among others. Threshold accepting is an iterative search process for developing near-optimal solutions to problems.…”
Section: Maximize Mdnmentioning
confidence: 99%
“…Threshold accepting (TA) is a deterministic version of another local search method, simulated annealing. Threshold accepting has been shown to be able to produce as good, or even better solutions, than simulated annealing (Dueck and Scheuer 1990, Bettinger et al 2002, Pukkala and Heinonen 2006. In Monsu software, TA uses the best of a set of random combinations of calculation units' treatment schedules as the initial solution.…”
Section: Optimisation Methodsmentioning
confidence: 99%
“…The advantage of heuristics is mainly due to the quickness of generating very good and feasible solutions to complex problems, once the heuristic is developed appropriately. Previous research including Bettinger et al [48] and Pukkala and Miina [31] have shown in forest management that quality solutions can be obtained using heuristics. If the quality of the solution is deemed high compared to exact solution techniques, then heuristics are the preferred solution technique.…”
Section: Heuristics Technique or Meta Modelsmentioning
confidence: 99%